Effect of Instructional Leadership on Teachers’ Effectiveness at Secondary School Level - Malik, Muhammad Irfan; Mehmood, Muhammad Faisal; Qamar, Abdul Hameed (Journal of Development and Social Sciences, 2025)
The study aimed to find out the effect of instructional leadership on teachers’ effectiveness at secondary school level. Instructional leadership is the way school heads facilitate the progression of teaching and learning by setting the school mission, encouraging staff to achieve the educational goals, and coordinate all the instructional activities in their schools. While teachers’ effectiveness involved the ability of teachers to recognize the needs of their students, choose the best teaching method, and select activities suitable for the student learning. By using the multi-stage sampling technique, 600 SSTs were selected from the district Bahawalnagar including 368 male teachers and 232 female teachers. Instructional leadership were determined through using the instructional leadership questionnaire (ILQ) developed by Akram et al. (2017) and teachers’ effectiveness was examined by using the teacher effectiveness scale (STEQ) which was also developed by Akram (2018). The study concluded that head teachers’ instructional leadership was an above average, while the level of teachers’ effectiveness was also an above average. The study also revealed the positive and significant relationship between the instructional leadership and teachers’ effectiveness (r=.65), while 48% variance in teachers’ effectiveness could also be explained through the head teachers’ instructional leadership. Further, the given study also added the limitation and suggestions.